2019
DOI: 10.1371/journal.pone.0214933
|View full text |Cite
|
Sign up to set email alerts
|

Water temperature drives phytoplankton blooms in coastal waters

Abstract: Phytoplankton blooms are an important, widespread phenomenon in open oceans, coastal waters and freshwaters, supporting food webs and essential ecosystem services. Blooms are even more important in exploited coastal waters for maintaining high resource production. However, the environmental factors driving blooms in shallow productive coastal waters are still unclear, making it difficult to assess how environmental fluctuations influence bloom phenology and productivity. To gain insights into bloom phenology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
163
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 163 publications
(179 citation statements)
references
References 93 publications
(121 reference statements)
14
163
1
1
Order By: Relevance
“…Microbial interaction networks during the bloom and non-bloom periods differ and complexity increases during phytoplankton blooms. Trombetta et al (2019) showed that in the same shallow coastal waters, increase in water temperature during spring triggers phytoplankton bloom. Here, we found that increases in phytoplankton biomass are responsible for profound modifications at the level of microbial interactions.…”
Section: Network Complexity Increases During Phytoplankton Bloommentioning
confidence: 99%
See 4 more Smart Citations
“…Microbial interaction networks during the bloom and non-bloom periods differ and complexity increases during phytoplankton blooms. Trombetta et al (2019) showed that in the same shallow coastal waters, increase in water temperature during spring triggers phytoplankton bloom. Here, we found that increases in phytoplankton biomass are responsible for profound modifications at the level of microbial interactions.…”
Section: Network Complexity Increases During Phytoplankton Bloommentioning
confidence: 99%
“…Apart from its ecological interest, it is a lagoon of economic relevance, mainly due to oyster farms representing 10% of the French production. Complementary data on hydrological parameters (water temperature, salinity, oxygen concentration, oxygen saturation and turbidity), meteorological parameters (air temperature, wind speed, wind direction, PAR, UVA and UVB) and corrected fluorescence of the chlorophyll a monitored at high frequency are available in open access in Mostajir et al (2018) and Trombetta et al (2019).…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations